Weak-form Efficient Market Hypothesis, Behavioural Finance and Episodic Transient Dependencies The Case of the Kuala Lumpur Stock Exchange - Lim, Kian-Ping; Liew, Venus Khim-Sen; Wong, Hock-Tsen (Munich University Library, 2003)
This study utilizes the windowed-test procedure of Hinich and Patterson (1995) to examine the data generating process of KLSE CI returns series. Unlike previous studies, the present one relates the evidence to the popular weak-form EMH and behavioural finance, with the hope of offering some plausible explanations to the controversy arises between these two camps. Our econometrics results indicate that linear and non-linear dependencies play a significant role in the underlying data generating process. However, these dependencies are not stable as the results suggest that they are episodic and transient in nature. Along the line of our interpretations, we are able to offer some plausible explanations as to why weakform EMH generally holds in KLSE, though the presence of linear and non-linear dependencies implies the potential of returns predictability. Specifically, these significant dependencies show up at random intervals for a brief period of time but then disappear again before they can be exploited by investors. Looking from a micro perspective, we are able to rationalize the co-existence of weak-form EMH and behavioural finance in KLSE when the statistical properties of random walk, linear and non-linear dependencies, which also co-exist in the time domain, are interpreted in the framework of information arrival and market reactions to that information.